THE HIDDEN CAUSES OF INFERTILITY DIAGNOSED AT TERTIARY CARE - Kaluarachchi, A; Senevirtne, H.R; Wijeratne, S.; Nelson, C; Rajapakse, S (My University)
Infertility affects 1 in 6 couples seeking a pregnancy. The causes of Infertility for these couples are numerous. Some of these causes are hidden and not detectable by routine diagnostic procedures. Many of these hidd :n causes are detectable only at the level of tertiary care management.